Human Capital dan Upah Dosen Perguruan Tinggi Negeri pada Pekerjaan Sampingan di Kota Makassar - Madris Madris (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
This study aims to determine the effect of human capital (education and work experience) on wages working on side jobs, either directly or the work productivity of lecturer at State University in Makassar. Sampel of 220 respondents was selected purvosive by population of lecturer PTN in the Makassar City minimally educated S2 degree and IIIC. By using SEM analysis (Structural Equation Model), the results showed that: (1) work experience and formal education PNS was given positive and significant impact on work productivity of lecturer. The implication lecturer competence is determined by factors of education and work experience. (2) However, only formal education have a significant effect on the wage side working, while the experience of working and labor productivity appears no effect. Gives an indication that there is no other way to fix the additional labor income lecturers, except by improving the competence through continuing education.